2022
DOI: 10.31234/osf.io/v2x5n
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two languages in one mind: insights into cognitive effects of bilingualism from usage-based approaches

Abstract: Bilingualism has been associated with changes in our language-related and domain-general cognition. However, it remains controversial whether bilingualism-related cognitive effects are robust and stable. Also, it is still unclear what about being bilingual causes the plasticity of cognitive processes. This article offers a selective overview of the literature on bilingualism and cognition. We will discuss results from studies which investigated sources of cognitive plasticity in bilinguals, using prominent bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…The professional interpreters were more efficient than the two matched groups in their resistance to a prepotent response at the later ages (Henrard and Van Daele, 2017). It is also possible that the difference between professional and non-professional bilinguals' cognitive effects is due to differences in the quantity and quality of their regular language use practices (Korenar et al, 2022). While the effect of aging in the present was clearly visible in processing speed, with slower response times for professional interpreters than both student groups, a similar difference was not observed in error rates, with equal accuracy for the professional interpreters as compared to the student groups.…”
Section: Inhibition In Interpretersmentioning
confidence: 97%
“…The professional interpreters were more efficient than the two matched groups in their resistance to a prepotent response at the later ages (Henrard and Van Daele, 2017). It is also possible that the difference between professional and non-professional bilinguals' cognitive effects is due to differences in the quantity and quality of their regular language use practices (Korenar et al, 2022). While the effect of aging in the present was clearly visible in processing speed, with slower response times for professional interpreters than both student groups, a similar difference was not observed in error rates, with equal accuracy for the professional interpreters as compared to the student groups.…”
Section: Inhibition In Interpretersmentioning
confidence: 97%
“…It is important to note that deviances in the HL usually go hand in hand with native competences in the ML. However, there are some studies that suggest a bidirectional influence of both languages, (e.g., van Rijswijk et al, 2017 ) and general differences in bilingual language processing compared to monolingual processing (Kroll and Gollan, 2014 ; Korenar et al, 2023 ). In their study covering different language contact situations including several HLs and MLs, Wiese et al ( 2022 ) demonstrate that not all deviances found in HL research can or should be related to effects of bilingualism.…”
Section: Introductionmentioning
confidence: 99%